A Durometer (Mammometer) for Objective Measurement Capsular Contraction Following Breast Implant Surgery. Issue 4 (December 2020) - Murphy, Tracey; Brown, Stephen; Brown, Tim
The importance of measuring breast firmness reproducibly to monitor postsurgical progress has been appreciated for many years. This study ascertains whether a durometer can be used to quantify capsular contraction and to provide an objective, reproducible measure of fibrosis around an implant. Patients with clinically detected Baker 3 or 4 capsules following breast augmentation underwent firmness measurements using a durometer prior to corrective surgery. Durometry was undertaken on both breasts by an operator who was blinded to the clinical diagnosis. Firmness measurements were taken in each breast quadrant and directly over the nipple-areolar complex on each side. In the study, 16 patients were included. Capsules presented 16 to 714 weeks following surgery (mean 217, standard deviation (STD) 205.4 weeks). Differences in pressure were demonstrated in all quadrants of the breast and at the nipple-areolar complex except the lower inner quadrant. All significant differences demonstrated a higher pressure in the encapsulated breast. The mean pressure in an encapsulated breast was 0.66 kPa (STD 0.25) and 0.46 kPa (STD 0.16) in the normal breast. The durometer can reproducibly describe changes in pressure associated with capsular contraction compared with the contralateral breast. It provides a means of objectively describing capsular contraction following breast augmentation surgery for research and patient care.